The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1088/1748-9326/11/5/054020
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between urban vegetation and surface urban heat islands: a case study in the Boston metropolitan region

Abstract: Many studies have used thermal data from remote sensing to characterize how land use and surface properties modify the climate of cities. However, relatively few studies have examined the impact of elevated temperature on ecophysiological processes in urban areas. In this paper, we use time series of Landsat data to characterize and quantify how geographic variation in Boston's surface urban heat island (SUHI) affects the growing season of vegetation in and around the city, and explore how the quality and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 47 publications
4
49
0
1
Order By: Relevance
“…Recent research has suggested that the growing season of vegetation in cities is longer compared with the surrounding rural regions because of UHI effects [9,17,26,27,33,34]. Our results support this conclusion, providing a refined characterization of interactions between composition and configuration of local LCLU types and spatial patterns of vegetation phenology.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent research has suggested that the growing season of vegetation in cities is longer compared with the surrounding rural regions because of UHI effects [9,17,26,27,33,34]. Our results support this conclusion, providing a refined characterization of interactions between composition and configuration of local LCLU types and spatial patterns of vegetation phenology.…”
Section: Discussionsupporting
confidence: 87%
“…Melaas et al [31,32] extended the algorithm in a way that allowed the detection of interannual variability in phenology and validated the method in North American temperate and boreal deciduous forest. These approaches have only recently been applied to urban areas [33,34], and there remain substantially unrealized potential for leveraging them to better understand how urbanization affects phenological changes. More importantly, landscape patterns not only reflect the urban development and their socioeconomic drivers [35][36][37], but also significantly influence UHI [38].…”
Section: Introductionmentioning
confidence: 99%
“…This also indicates that base pair and software selection may lead to different results than when looking at features or specific locations within the municipality. This supports previous findings that EOS in urban vegetation patches is influenced by the percent impervious surface of surrounding patches [56].…”
Section: End Of Seasonsupporting
confidence: 93%
“…This coincides with the case study by Melaas et al [56], which showed that the amount of impervious surface area in surrounding vegetation patches influences the timing of SOS. Although we do not show a clear trend with the difference in SOS growing as mean percent imperviousness does, for all three selection methods the difference in mean days becomes larger between urban and exurban areas for the two most developed classes when compared to the two least developed classes.…”
Section: Start Of Seasonsupporting
confidence: 92%
“…However, due to the sparse distribution of observation stations, spatially continuous analysis is difficult. To solve this problem, the use of satellite data for the detection and assessment of SUHIs has been attempted [22][23][24][25][26]. Remote sensing data have wall-to-wall continuous coverage of urban areas [27].…”
Section: Introductionmentioning
confidence: 99%